Perceived barriers and facilitators to infection prevention and control in Dutch residential care facilities for people with intellectual and developmental disabilities: a cross-sectional study - Famke Houben; Casper DJ den Heijer; Nicole HTM Dukers-Muijrers; Claudia Smeets-Peels; Christian JPA Hoebe (BMC, 2024)
Abstract Background Adequate implementation of infection prevention and control (IPC) in residential care facilities (RCFs) for people with intellectual and developmental disabilities (IDDs) is crucial to safeguarding this vulnerable population. Studies in this field are scarce. This study aimed to identify perceived barriers to and facilitators of IPC among professionals working in these settings, along with recommendations to improve IPC, to inform the development of targeted interventions. Methods We administered an online questionnaire to 319 professionals from 16 Dutch RCFs for people with IDDs (March 2021-March 2022). Perceived multilevel barriers and facilitators (guideline, client, interpersonal, organisational, care sector, and policy level) were measured on a 5-point Likert scale (totally disagree-totally agree). Recommendations were assessed using a 5-point Likert scale (not at all helpful-extremely helpful), supplemented by an open-ended question. Barriers, facilitators, and recommendations were analysed by descriptive statistics. Open answers to recommendations were analysed through thematic coding. Results Barriers to IPC implementation included the client group (e.g., lack of hygiene awareness) (63%), competing values between IPC and the home-like environment (42%), high work pressure (39%), and the overwhelming quantity of IPC guidelines/protocols (33%). Facilitators included perceived social support on IPC between professionals and from supervisors (90% and 80%, respectively), procedural clarity of IPC guidelines/protocols (83%), and the sense of urgency for IPC in the organisation (74%). Main recommendations included the implementation of clear IPC policies and regulations (86%), the development of a practical IPC guideline (84%), and the introduction of structural IPC education and training programmes (for new staff members) (85%). Professionals also emphasised the need for IPC improvement efforts to be tailored to the local care context, and to involve clients and their relatives. Conclusions To improve IPC in disability care settings, multifaceted strategies should be adopted. Initial efforts should involve clients (and relatives), develop a practical and context-specific IPC guideline, encourage social support among colleagues through interprofessional coaching, reduce workload, and foster an IPC culture including shared responsibility within the organisation.